Opportunities and Challenges of Artificial Intelligence in English Language Education at Higher Education Institution - Illananingtyas, Tenika (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to examine Artificial Intelligence (AI) in English language teaching at higher education. The research focuses on the opportunities and challenges in English language teaching. A qualitative approach using phenomenological methods was employed to explore the experiences of lecturers in utilizing AI during the language learning process, through surveys and in-depth interviews. Data were collected via questionnaire created using Google Forms and distributed to English lecturers. The research sample consisted of 10 English lecturers from East Java. Analysis of the questionnaires and interview transcripts revealed that the presence of AI technology has introduced both opportunities and challenges in English teaching and learning. AI has transformed the way English is taught in higher education. Lecturers utilize various AI tools for purposes such as enhancing learning motivation, answering and solving queries, paraphrasing, and reviewing literature. The study also highlighted the benefits of AI in teaching and learning. However, AI also presents new opportunities and challenges for the future of English language teaching. Therefore, English lecturers are encouraged to continuously improve their digital skills to adapt to these advancements.